Islam Kejawen dalam Perspektif Islam Nusantara: Akulturasi, Nilai dan Praktik Keagamaan - Putri, Rita Nabila Anisa (Javano Islamicus, 2026)
Islam Kejawen is a form of diversity within Javanese society that emerged from the encounter and mutual influence between Islam and Javanese culture. This article discusses the origins of Islam Kejawen, its distinctive characteristics, and the reasons behind the continued relevance of its practices in Javanese society. The article employs a literature review or library research method by collecting references from journals, e-books, and recent studies on Javanese religious traditions. The findings show that the process of Islamization in Java did not bring about immediate and complete change, but instead occurred gradually through cultural approaches. This process gave rise to various practices such as slametan, ruwatan, mitoni, and many other traditional rituals, which function not merely as rituals but also as means for maintaining social cohesion and cultural identity. However, Islam Kejawen has faced criticism from modernist groups who consider its practices inconsistent with Islamic teachings. On the other hand, Islam Kejawen remains significant in the study of Islam Nusantara, as it demonstrates that religious teachings can coexist with local culture without conflict. Overall, this article shows that Islam Kejawen is a dynamic phenomenon that continues to evolve and occupies a distinct space in the socio-religious life of Javanese society.